The State of food and agriculture 1972 - Food and Agriculture Organisation of the United Nations (Rome : Food and Agriculture Organisation of the United Nations, 1972)
Because 1971 was the first year of the Second United Nations Development Decade, the performance of the world's agriculture must inevitably be assessed against the targets set by the international community for this period. Unfortunately it was not a particularly good year for the agricultural sector in the developing countries. That world production maintained its long-term annual increase of about 3 percent was due to substantial expansions in the developed countries, where incomes are relatively high and nutrition generally adequate. In the developing countries the rise in production was between 1 and 2 percent, which is much less than in recent years and well below the target of the Second Development Decade of an average annual increase of 4 percent. For 1972, preliminary information suggests that no acceleration has occurred in this rate of increase.
lje 28/06/17
Ref.
Keywords: Food production; Agriculture; Trade